Pelanggaran Kode Etik Anggota Polri dalam Tindak Pidana Korupsi - Miftachul Mujadi; M Syahrul Borman (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2023)
This article aims to find out the reasons behind members of the Indonesian National Police in abusing office power by committing acts of corruption and the process of applying sanctions to the code of ethics against members of the Indonesian National Police who commit acts of corruption. This journal uses normative research methods, namely by conducting literature studies through literature and legal norms. The results of this study indicate that the professional code of ethics within the Indonesian National Police cannot be implemented optimally. That until now there are still many violations committed by members of the Indonesian National Police, including acts of corruption which constitute an abuse of office power and violate the professional code of ethics within the Indonesian National Police.